Analysis of the Role of Muhammadiyah in Solidarity Buying and Empowering UMKM in the Covid 19 - Abizar Abizar; M. Sholihin; Nina Ramadhani Wulandari (ITB AAS INDONESIA Surakarta, 2022)
Muhammadiyah has a role in the life of the Indonesian nation. Muhammadiyah has a position, contribution, and an important role in enlightening the condition of the nation. Muhammadiyah is a religious organization that always adheres to good deeds, not only in matters of religion, but also seeks to improve welfare, by playing an active role in community empowerment, including UMKM. The role of Muhammadiyah focuses on all aspects of social and economic life. Muhammadiyah is certainly a very valuable asset, especially when the community is in difficult conditions. Covid-19 causes economic activity and sales of goods in all sectors to decline. Covid 19 suppresses the level of welfare of the community, UMKM, and workers. This condition requires the role of all parties, the government, the community and various groups, the existence of efforts and strategies as well as the role of Community Organizations including Muhammadiyah to improve conditions, carry out social solidarity, mutual cooperation, and community empowerment are highly expected. Seeing this condition, it is important to conduct related research; Analysis of the Role of Muhammadiyah in Solidarity Buying and Empowerment of UMKM so that the evaluation and role of Muhammadiyah are effective and efficient for the Indonesian people and become other pilot materials. Muhammadiyah Lampung has been proven to have played an active role in the solidarity buying program and empowering UMKM during the COVID-19 period on health, economy and other social communities. The role of Muhammadiyah focuses on aspects of the impact of health and food security, several business charities of Muhammadiyah in Lampung work hand in hand with stakeholders to overcome the impact of covid 19. However, the solidarity buying program and the empowerment of UMKM have not been significant as a flagship program in a massive and comprehensive manner. This program is carried out only for business charities that are engaged in the economy, not yet part of the PWM Lampung's firm instructions, the nature of the solidarity buying movement and the empowerment of UMKM is to appeal to business charities and the community.